A Comparative Analysis of the Legislation on Maritime Militia Between China and Vietnam. (27th October 2022) - Cui, Haoran; Shi, Yubing
Abstract: In recent years, the maritime militia and their activities in the South China Sea have attracted mounting attention from the international community. To date, only China and Vietnam have established rules relating to maritime militia. The maritime militia systems in both China and Vietnam result from national traditional militia systems and are extended reflections of the "People's War" ideology in the field of modern defense. They are similar in aspects such as their definitions and nature, type of activities and scope, and leadership. Also, both militias play an affiliated role in their protection of maritime rights and military systems. Nonetheless, there are distinct differences between the legislation of maritime militia in China and Vietnam, particularly in relation to the political role they play, welfare and treatment, and punishment mechanisms. Through the comparison of the legislation on maritime militia in China and Vietnam, this article aims to define the legal status of maritime militia and to propose approaches to improving China's legislation on maritime militia.